Inflectionally Sensitive Web Search in Croatian using Croatian Lemmatization Server - Tadić, Marko (Array, 2006)
Web search engines are becoming everyday commodity but still they are mainly oriented towards English. Other languages, with their different word structures, are not represented well with available web search engines. We present one solution for a morphologically sensitive search engine which enables the Croatian-speaking users to use query words more naturally and get the results that cover all and only all word-forms of searched words.